Emprego público no Brasil: Aspectos históricos, inserç\~ao no mercado de trabalho nacional e evoluç\~ao recente - Fernando Augusto Mansor de Mattos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper presents a description of the Brazilian public employment trend since the middle of the twentieth century. Its objective is to stress the causes of the increasing in public employment levels and also its role to the Brazilian labor market transformations since then. In this paper, public employment includes direct and indirect administration. Usually, the international organizations (like, for example, ILO, OECD and World Bank) utilize the same methodology to measure public employment. Thus, the data on Brazilian public employment is comparable with the same variables for other countries. Furthermore, we considered formal and also informal labor in private sector as the denominator of the share of public employment over total occupation (total occupation encompasses public plus private sector jobs). This procedure of measuring the share of public employment is the most common in the international literature. The methodology adopted in this study to measure the share of public employment also allows a consistent international comparison.
Keywords: J21; J10; J45; 330; Öffentlicher Dienst; Arbeitsmarkt; Brasilien